BISOPROLOL AND METFORMIN IN PATIENTS WITH ARTERIAL HYPERTENSION AND METABOLIC SYNDROME - V. A. Nevzorova; N. V. Zakcharchuk; O. V. Nastradin; O. G. Pomogalova (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To compare efficacy of bisoprolol and bisoprolol+metformin combination in patients with arterial hypertension (AH) and metabolic syndrome (MS).Material and methods. 20 patients with AH and MS were involved in the study. They were randomized in 2 groups, 10 patients in each group. Patients of the 1st group received bisoprolol. Patients of the 2nd group received combination of bisoprolol and metformin. Blood pressure (BP), body mass index (BMI), carbohydrate metabolism, lipid profile, microalbuminuria (МАU) level was determined before, within and at the end of 24-week treatment.Results. Both treatments resulted in similar reduction in BP. Reduction of BMI and insulin plasma concentration was more significant in patients received combined therapy. Both treatments improved lipid profile and reduced MAU.Conclusion. Bisoprolol has positive effect on pathogenic mechanisms of AH and MS. Metformin additionally improves carbohydrate and lipid metabolism.